2020
DOI: 10.1055/s-0040-1708865
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Removal of Modified Vertical Uterine Compression Sutures due to Postoperative Focal Pain

Abstract: AbstractPreviously we reported laparoscopic removal of compression sutures due to uterine ischemia and related pain, which has two of the difficult aspects: (1) maneuvering the curved needle to perform compression suturing in the narrow surgical field, and (2) distinguishing between the threads of the cesarean section wound sutures versus the vertical compression sutures during removal, as the threads are the same white color. We performed vertical compression sutures for intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The threads of Matsubara-Yano UCS 1 were successfully removed under laparoscopy. Suzuki et al 4 also reported successful removal of the threads. In both reports, the threads were removed due to some adverse events caused by UCS.…”
Section: Uterine Compression Suture: Some Procedures To Reduce Necros...mentioning
confidence: 95%
“…The threads of Matsubara-Yano UCS 1 were successfully removed under laparoscopy. Suzuki et al 4 also reported successful removal of the threads. In both reports, the threads were removed due to some adverse events caused by UCS.…”
Section: Uterine Compression Suture: Some Procedures To Reduce Necros...mentioning
confidence: 95%